"Courting Is Like Trading Horses, You Have to Keep Your Eyes Open": Gender-Related Proverbs in a Peasant Society in Northern Sweden - Andersson, Daniel (Journal of Northern Studies, 2013)
Proverbs offer insights into normative symbolic systems of meaning. In this article, proverbs collected in Northern Sweden that mirrors an older agrarian environment are studied with a specific subset of such a normative meaning system in focus: masculinity and femininity. The analysis is centered on three important domains of human experience: The Marriage Market, The Household and The Sexuality. It is argued that the gender conceptions found in the proverbs form a system of gender hegemony, with hierarchically superiormasculinity and hierarchically subordinate femininity. Furthermore, a possible cultural model found in the proverbs, that of The Successful Household, is outlined and discussed.